Tobacco Use Cessation and Prevention – A Review - Shaik, Sabiha Shaheen (J Clin Diagn Res, 2016)
Tobacco use is a major preventable cause of premature death and disease, currently leading to over five million deaths each year worldwide. Smoking or chewing tobacco can seriously affect general, as well as oral health. Oral health professionals play an important role in promoting tobacco free-lifestyles. They should counsel their patients not to smoke; and reinforce the anti-tobacco message and refer the patients to smoking cessation services. Dentists are in a unique position to educate and motivate patients concerning the hazards of tobacco to their oral and systemic health, and to provide intervention programs as a part of routine patient care. Tobacco cessation is necessary to reduce morbidity and mortality related to tobacco use. Strategies for tobacco cessation involves 5 A’s and 5 R’s approach, quit lines and pharmacotherapy. Additionally, tobacco cessation programs should be conducted at community, state and national levels. Various policies should be employed for better tobacco control. Governments should implement the tobacco control measures to reduce the prevalence of tobacco use and exposure to tobacco smoke. In addition, there should be availability of leaflets, brochures, continuing patient education materials regarding tobacco cessation.